SUKUK MURABAHAH: A MECHANISM TO FUND INFRASTRUCTURE PROJECTS IN NIGERIAN TERTIARY INSTITUTIONS - Muhammad Duku (Airlangga International Journal of Islamic Economics and Finance, 2023)
Developed countries have actively engaged in producing and providing infrastructural facilities at all levels of development. The demands for infrastructure investment in developing nations quickly attract the country’s attention for the operation of organizational structures and the management of societal needs (e.g roads, bridges, power, education, transport, health care services, communication, technology, and many other sectors). In this regard, countries worldwide are seeking a way to increase their economic flow via infrastructure. In Nigeria, financing education became a bottleneck as a result of the tertiary institutions in the country lacking infrastructure which in consequence affected the growth and development of the institutions towards producing qualified-minded trained students in almost all fields of study. Therefore, this paper is to conceptually investigate how Sukuk Murabahah can be used to fund infrastructure projects in Nigerian universities. The study concludes that Sukuk Murabahah will play a significant role in financing and uplifting the standard of Nigerian tertiary institutions and brings about national development. Therefore, the study recommends that promoters of Sukuk should create more awareness about its availability, security, and minimal risk so that the government at all levels and corporate entities can benefit from the service. Governments at all levels and corporate entities should be encouraged to patronize or adopt Sukuk as their financing option due to its features of providing social and economic benefits to the issuer. The existing legal and regulatory framework should always be conformed with and developed to remain unfailing with time and space.